MON-515 Lack Of Association Between Bone Mineral Density And Breast Arterial Calcification: The Minerva Study - Iribarren, Carlos (J Endocr Soc, 2019)
Background: Prior studies have documented inverse associations of bone mineral density (BMD) with coronary and extra-coronary vascular calcification, indicating a biological interplay between bone and vascular systems. However,the relation between BMD and breast arterial calcification (BAC) remains controversial. This study aims to correlate BMD status with presence and severity of BAC in a large sample of post-menopausal women free of clinical cardiovascular disease (CVD) at baseline. Methodology: We used data from the MultIethNic study of brEast aRterial calcium gradation and cardioVAscular disease (MINERVA), a multiethnic cohort of women aged 60 to 79 years at baseline (10/24/2012-2/13/2015) who were free of symptomatic CVD, all recruited after mammography screening at Kaiser Permanente of Northern California (KPNC). The sample available for analyses with complete data on BMD, BAC and covariates was 1,273 (mean ± SD age=67 ± 4, 52% white, 18% Asian, 15% African-American and 12% Latina). BMD assessments in spine, hip and head of the femur up to 3 years prior to the baseline exam was done with dual-energy X-ray absorptiometry (DXA) as part of routine medical care and participants were categorized into 3 groups: normal, osteopenia and osteoporosis using WHO criteria. A BAC continuous mass score (mg) was obtained from digital mammograms using a validated densitometry method. BAC presence was BAC score > 0 mg, and severe BAC was defined as BAC score > 20 mg. Data was analyzed using the Chi-Square for contingency tables and multivariable logistic regression. Results: Overall, 54% (686/1,273) had osteopenia and 21% (267/1,273) had osteoporosis. The prevalence of BAC > 0 mg did not differ significantly by BMD status (Chi-Square=0.03;2df;p=0.98): it was 30% (97/320) among women with normal BMD, 31% (212/686) among women with osteopenia, and 31% among women with osteoporosis (82/267). Likewise, the prevalence of BAC > 20 mg did not differ significantly by BMD status (Chi-Square=2.4;2df;p=0.65): it was 5% (16/320) among women with normal BMD, 3% (23/686) among women with osteopenia, and 5% among women with osteoporosis (13/267). The odds ratios (ORs) of BAC > 0 vs. BAC=0 mg after adjustment for age, race, education level, BMI, smoking, alcohol consumption, total physical activity score, diabetes, hypertension, calcium supplement use, menopausal hormone therapy, history of breast feeding and parity were 1.09 (95% CI, 0.81-1.47) for osteopenia and 1.05 (95% CI, 0.70-1.56) for osteoporosis. The adjusted OR for BAC > 20 vs BAC ≤20 mg were 0.96 (95%CI, 0.48-1.94) for osteopenia and 1.58 (95 CI, 0.64-3.93) for osteoporosis. Conclusion: Our findings do not support an association of either osteopenia or osteoporosis with BAC presence or severity.